Potential Vectors of Xylella fastidiosa in Portugal vineyards - Reis, Carlos (2018)
Xylella fastidiosa was recently detected in vineyards from Spain. This phytopathogenic bacterium is a threat also in Portugal where the vineyards is a main crop. It is transmitted by xyllem-feeding insects basically belonging to Hemiptera Cicadomorpha. However, the knowledge about these insects distribution in Portugal is scarce. In this context, the goal of this work was to identify the biodiversity of Cicadormorpha in vineyards from Portugal. For that, in 2018, 23 vineyards with ground cover with vegetation and from 5 different regions in Portugal (Trás-os-Montes DOC; Vinho Verde DOC, Bairrada 1 DOC, Bairrada 2 DOC, and Setúbal DOC), were sampled for adults during three dates (beginning of July, mid September and mid October). Sampling was performed in the ground and in the aerial part of the vines. In the ground, a total of 10 samples of 10 sweepings were collected in each vineyard. In the aerial part of the vines, 10 samples of 50 sweepings in 3 lines of the vineyard were performed. Each sample was kept in a plastic bag and frozen for further identification. Only insects belonging to the Auchenorrhyncha suborder were studied. At the beginning of July a total of 1705 Auchenorryncha were collected. From them, 550 were Fulgoromorpha and 1152 Cicadomorpha, being 22 potential vectors of X. fastidiosa. Results of the second and third dates are currently under evaluation.